2017
DOI: 10.1111/jop.12531
|View full text |Cite
|
Sign up to set email alerts
|

Does cell phone use increase the chances of parotid gland tumor development? A systematic review and meta‐analysis

Abstract: Initial screening included 37 articles, and three were included in meta-analysis. Using three independent samples including 5087 subjects from retrospective case-control studies, cell phone use seems to be associated with greater odds (1.28, 95%- confidence interval: 1.09-1.51) to develop salivary gland tumor. Results should be read with caution due to the limited number of studies available and their retrospective design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…[7] Since then, subsequent case-control studies have reported inconsistent findings regarding the association between cellular phone use (use vs. never or rarely use) and tumor risk, similar to our previous findings. Since we published our meta-analysis in 2009, six meta-analyses [61][62][63][64][65][66] have reported the associations between cellular phone use and risk of brain tumors or head and neck tumors, mainly glioma and salivary gland tumors. Among them, four meta-analyses concluded that there was a statistically significant increased risk of glioma among heavy or long-term (over 10 years) mobile phone users in meta-analyses of 10 to 12 case-control studies [61,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…[7] Since then, subsequent case-control studies have reported inconsistent findings regarding the association between cellular phone use (use vs. never or rarely use) and tumor risk, similar to our previous findings. Since we published our meta-analysis in 2009, six meta-analyses [61][62][63][64][65][66] have reported the associations between cellular phone use and risk of brain tumors or head and neck tumors, mainly glioma and salivary gland tumors. Among them, four meta-analyses concluded that there was a statistically significant increased risk of glioma among heavy or long-term (over 10 years) mobile phone users in meta-analyses of 10 to 12 case-control studies [61,[64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…1 Although there are some theories on possible indicators (such as mobile phones), no certain evidence has been presented as yet. 37,38 It is obvious that early surgical procedure would be safer in the majority of parotid gland tumors and proper surgical qualification is therefore critical. Until now there has been no serum biomarker for these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…While independent meta-analyses including several types of intra-cranial tumors are in accordance with those results 4 , 5 , Röösli et al 6 found no association between glioma risk and MP use. Regarding salivary gland tumors, both conclusions have been reached: no association 4 , 7 , and association (mild but significant) 8 . Miller et al 9 proposed that the International Agency for Cancer Research (IARC) should change the classification of RF EMF from MP and other wireless devices from its current IARC Group 2B (possibly carcinogenic) to Group 1 (carcinogenic), whereas organizations such as the Food and Drugs Administration from the USA 10 or the Swedish Radiation Safety Authority 11 have come to the exact opposite conclusion.…”
Section: Introductionmentioning
confidence: 97%